Accountability of Islamic Non-Governmental Organizations in Indonesia: A Netnographic Study (Jati: Jurnal Akuntansi Terapan Indonesia, 2024)
This study aims to analyze the online public's views on the accountability of the XYZ Foundation (XYZ), an Islamic non-government organization (NGO). This qualitative research uses netnography methods and primary data in the form of Twitter tweets with the trending hashtag #JanganPercayaXYZ. This research was carried out not long after the XYZ case emerged. The study includes an examination of relevant supporting documents, for example, the financial statement of XYZ. Data analysis was conducted in four stages: investigation, interaction, immersion, and integration. The results show that the public's views indicate that XYZ lacks accountability and transparency because the campaign is not in line with reality. There are too many cuts in donations, which has an impact on damaging public trust. XYZ is considered to be using religion and humanity to gain attention and empathy from donors. However, these do not deny XYZ's great contribution and performance in humanitarian affairs. These results have implications for the need to improve Islamic philanthropic institutions' regulation, governance, and accountability, as well as the prudence and selectivity of donors in donating through similar institutions. This study contributes to the literature on accountability in Islamic NGOs by utilizing netnography and data from social media.